2005
DOI: 10.1128/aac.49.6.2528-2532.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP3A1(23) Induction on Clarithromycin Pharmacokinetics in Rats with Diabetes Mellitus

Abstract: After intravenous and oral administration of clarithromycin at a dose of 20 mg/kg of body weight to rats with diabetes mellitus induced by alloxan (DMIA) and diabetes mellitus induced by streptozotocin (DMIS), the area under the curve values were significantly smaller than those of respective control rats. The in vitro intrinsic clearance values for the disappearance of clarithromycin were significantly faster in both rats with DMIA and rats with DMIS than in control rats. The above data suggested that metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…It was reported that the enzyme activity, protein expression, and/or mRNA level of hepatic CYP3A1 (Kim et al, 2005b;Borbás et al, 2006) and CYP3A2 in streptozotocin (STZ)-induced diabetic rats (Shimojo et al, 1993;Borbás et al, 2006) were higher than those in control rats. Several reports showed that the up-regulation of hepatic CYP3A in diabetic rats may contribute to the faster clearance and lower area under the concentration-time curve (AUC) value of drugs, such as telithromycin and clarithromycin (Kim et al, 2005b;Lee and Lee, 2008). It is known that the small intestine also plays an important role in first-pass extraction of orally ingested xenobiotics.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the enzyme activity, protein expression, and/or mRNA level of hepatic CYP3A1 (Kim et al, 2005b;Borbás et al, 2006) and CYP3A2 in streptozotocin (STZ)-induced diabetic rats (Shimojo et al, 1993;Borbás et al, 2006) were higher than those in control rats. Several reports showed that the up-regulation of hepatic CYP3A in diabetic rats may contribute to the faster clearance and lower area under the concentration-time curve (AUC) value of drugs, such as telithromycin and clarithromycin (Kim et al, 2005b;Lee and Lee, 2008). It is known that the small intestine also plays an important role in first-pass extraction of orally ingested xenobiotics.…”
Section: Introductionmentioning
confidence: 99%
“…For example, faster clearance and a lower area under the concentration-time curve (AUC) of telithromycin and clarithromycin were shown in diabetic rats (Kim et al, 2005;Lee and Lee, 2008). In another study, diabetes induced increased the plasma concentration of verapamil after oral administration .…”
Section: Introductionmentioning
confidence: 95%
“…Clarithromycin and S. boulardii were dissolved in saline. The dose selection of the test drugs were according to the previous in vivo rat studies (Buts et al, 1990;Kim et al, 2005).…”
Section: Methodsmentioning
confidence: 99%